Sosialisasi Pengenalan dan Strategi Pengembangan Usaha Mikro Kecil Menengah (UMKM) Desa Cimaung - Popi Dayurni; Kurniati Rahmadani (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in national economic growth. MSMEs are actually nothing new. However, there are still many rural communities who do not know what MSMEs are and what kinds of businesses are categorized as Micro, Small and Medium Enterprises. Besides that. Village communities who have become MSME actors experience several problems in developing MSMEs. This lack of knowledge about MSME development strategies is one of the factors causing MSMEs to be difficult to develop in rural areas. Cimaung Village has one MSME in the form of processed tempe. Where this tempeh is processed into various flavored tempeh chips. This is quite good because there has been innovation in the tempe processing. However, the marketing process is still limited, traditionally done in the physical market. Based on this, it is necessary to disseminate information regarding the introduction and strategies regarding the development of this MSME. This socialization aims to provide a brief introduction to MSMEs to people who are not perpetrators of MSMEs, and also provide information on what strategies can make MSMEs grow